Enhancing Elementary Students' Academic Achievement Through the Scramble Learning Model - Nugraha, Ferry Ichsan; Nugraha Permana Putra; Hema WIdiawati (Papanda Publisher, 2025)
Traditional lecture-based teaching methods in Indonesian elementary schools often result in passive learning environments and suboptimal academic achievement, particularly in integrated subjects requiring cultural understanding. The scramble learning model, an interactive game-based approach involving the arrangement of scrambled words and sentences, has emerged as a promising pedagogical strategy to enhance student engagement and learning outcomes. This study investigated the effect of the scramble learning model on academic achievement among fourth-grade students learning the theme